A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • one year ago

Solve the system using the method of your choice: y = 3x – 4 2x + 4y = 26

  • This Question is Closed
  1. texaschic101
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    substitution ok with you ?

  2. texaschic101
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    y = 3x - 4.....so we sub in 3x - 4 for y back into the other equation 2x + 4y = 26 2x + 4(3x - 4) = 26 --- distribute through the parenthesis 2x + 12x - 16 = 26 --- add 16 from both sides 2x + 12x = 26 + 16 -- combine terms 14x = 42 x = 42/14 x = 3 now sub 3 in for x in either equation to find y y = 3x - 4 y = 3(3) - 4 y = 9 - 4 y = 5 we can even check our answers 2x + 4y = 26 2(3) + 4(5) = 26 6 + 20 = 26 26 = 26 (correct) so x = 3 and y = 5....or (3,5)

  3. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thank you!:)

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.